2022
DOI: 10.1039/d1sc05662j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing proline-rich antimicrobial peptide action by homodimerization: influence of bifunctional linker

Abstract: Homodimerization of a proline-rich antimicrobial peptide via bioconjugation to perfluoroaromatic linkers confers increased antimicrobial, antibiofilm and immunomodulatory activity. The dimers are promising new therapeutic leads against WHO priority multidrug resistant bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 52 publications
(63 reference statements)
1
35
0
Order By: Relevance
“…It also enabled us to compare the results obtained here with the ones previously obtained with the pre-formulation procedure, in which the thiol-terminated peptides were grafted on the polymer chain through Michael addition [12]. Indeed, when dealing with peptides, choice of the linker is not trivial and without consequences, since even the slightest modification can alter the peptide's behavior [24,25]. It has been notably recently highlighted with radiolabeled peptide derivatives, for which the chelate conjugated to the peptide demonstrated a significant influence [26,27].…”
Section: Discussionmentioning
confidence: 70%
“…It also enabled us to compare the results obtained here with the ones previously obtained with the pre-formulation procedure, in which the thiol-terminated peptides were grafted on the polymer chain through Michael addition [12]. Indeed, when dealing with peptides, choice of the linker is not trivial and without consequences, since even the slightest modification can alter the peptide's behavior [24,25]. It has been notably recently highlighted with radiolabeled peptide derivatives, for which the chelate conjugated to the peptide demonstrated a significant influence [26,27].…”
Section: Discussionmentioning
confidence: 70%
“…This dual mode of action of PP30, membrane lysis and DnaK activation, is novel and unreported for other native PrAMPs. Interestingly a dimeric form of the artificial PrAMP Chex-Arg20, A3-APO ( Szabo et al, 2010 ), has been shown to be predominantly membrane-lytic ( Li et al, 2017 ; 2022 ). The dual mode of action of PP30 has not however resulted in observable MICs in the assays here which may be due to a range of factors.…”
Section: Resultsmentioning
confidence: 99%
“…Class I PrAMPs, such as Bac7, Onc112, pyrrhocoricin, and metalnikowin, interfere with the initial step of translation to block the peptide transferase center and the peptide exit channel of the ribosome [128], whereas class II PrAMPs, such as apidaecin 1b and Api137, act during translation termination and inhibit protein synthesis by trapping release factors on the 70S ribosome following hydrolysis of the nascent polypeptide chain [129]. There are quite a few recent studies on PrAMPs, which attempt to enhance the antibacterial activity of PrAMPs against bacteria, even drug-resistant bacteria, through de novo synthesis, chemical modification and other methods [130][131][132]. A recent study showed that the PrAMP dimers produced by the bifunctional linker significantly enhanced their antibacterial and anti-biofilm activities against a variety of Gram-negative bacilli, including drug-resistant Acinetobacter baumannii strains [132].…”
Section: Amps Acting On Intracellular Targetsmentioning
confidence: 99%